Pendayagunaan Lahan Sawah Puso Akibat Rob Untuk Budidaya Ikan Nila Salin di Kelurahan Padukuhan Kraton Kota Pekalongan - M. Bahrus Syakirin; Ashari Fahrurrozi; Tri Yusufi Mardiana; Linayati Linayati; Nauval Rabbani; Abi Ardana; Erika Sari Rosiana (Universitas Muhammadiyah Manado, 2023)
Global warming causes one of the impacts in the form of tidal floods which harm the community because the rice fields for planting rice become unusable. An alternative land use used in community service is the aquaculture of saline tilapia in floating cages in the rice field area of Puso. The purpose of this activity is to provide knowledge to the public regarding tilapia fish farming with fixed cages and can be applied for the welfare of their income. The method used is in the form of counseling and direct observation to determine areas that will be used for piloting. The results of the service showed an increase in community knowledge with questionnaires from 38% to 92%. As well as the enthusiasm of the questions asked indicates that community service is running as it should.